Red Glow : Yugoslav Partisan Photography and Social Movement, 1941–1945 - Konjikušić, Davor (2021)
Davor Konjikušić provides an in-depth presentation and contextualization of the photographs created by Yugoslav partisans between 1941 and 1945. In doing so, the author is not only interested in presenting the photographs from an aesthetic perspective, but in the history of their use and function within one of the biggest anti-fascist movements in Europe during the Second World War.